Theory of Learning Cognitivism and Islamic Education - Windi Pratiwi Yusdar; Nur Afifah; Muh. Ridwan; Nur Oktaviani; Saprin (al-Afkar, Journal For Islamic Studies, 2025)
This research examines the integration of cognitivism learning theory in the context of Islamic education to optimize the learning process. The theory of cognitivism which emphasizes students' internal mental processes has significant relevance to the concept of Islamic education which prioritizes developing the potential of reason and spirituality. Through a qualitative approach with literature study methods, this research analyzes how the principles of cognitivism in Islamic educational prospective create meaningful learning. The results of the study show that cognitivism theory is in line with Islamic teachings which encourage the use of reason to understand science. The learning process in Islamic education can be enriched with cognitivism strategies such as information processing, the formation of knowledge schemes, and the development of metacognitive abilities. This integration allows students to not only understand the material in depth, but also develop critical thinking skills while still upholding Islamic values. Apart from the convergence between the two, there is also a divergence towards the implementation of cognitivism theory and Islamic education has the potential to create more effective learning. This research provides theoretical and practical contributions to the development of learning models in Islamic education that accommodate students' cognitive development without ignoring Islamic values.